The Effect of Variable Doses of Imipramine and Amitriptyline on Learning and Memory - JO, Asuquo; SE, Oyama; Samuel, Seriki A (Archives of Pharmacy and Pharmaceutical Sciences, 2024)
This study compares the effect of imipramine and amitriptyline on learning and memory. Thirty-five (35) healthy Swiss white (CD1) mice of both sexes weighing 18 g - 30 g were randomly divided into 5 groups (n = 7). Mice in group 1 (control) were administered 0.9% normal saline orally, while mice in groups 2 and 3 were treated with low (1.8 mg/kg) and high (3.7 mg/kg) doses of imipramine, groups 4 and 5 were treated with low (1.8 mg/kg) and high (3.7 mg/kg) of amitriptyline respectively. Treatment was for 21 days before tests. All animals were tested using the Morris Water Maze (MWM) and Novel Object Recognition Task (NORT) to assess visuospatial learning and memory as well as cognitive learning and memory. The results obtained from the Morris Water Maze during the acquisition training showed that the swim latencies were significantly lower (p < 0.05) in the amitriptyline low-dose group compared to the control group. During the reversal training, the swim latencies were significantly lower (p < 0.05) in the test groups compared to the control group. The result for the retention quadrant in the probe trials showed a significant decrease (p < 0.05) in the northeast quadrant in the test groups compared to the control group, with no significant difference in the visible platform day of the Morris Water Maze in the test groups compared to the control group. In the novel object recognition task, the short-term index of habituation was significantly lower (p < 0.05) in the low-dose imipramine and low-dose amitriptyline compared to the control group, the results also showed a significant increase (p < 0.05) in amitriptyline high dose group compared to imipramine and amitriptyline low dose group and the control group. The index of discrimination showed no significant difference among all groups. The long-term index of habituation and discrimination in the memory test showed a significant decrease (p < 0.05) in all the test groups compared to the control group. The results suggest that imipramine and amitriptyline impaired cognitive memory and enhanced visuospatial learning and memory functions.